Pelvic Pain of Pudendal Nerve Origin: Surgical Outcomes and Learning Curve Lessons - Dellon, A. Lee; Coady, Deborah; Harris, Dena (Journal of Reconstructive Microsurgery, 2015)
Purpose When pudendal nerve dysfunction fails to improve after medical and pelvic floor therapy, a surgical approach may be indicated. “Traditional,” “posterior,” transgluteal nerve decompression fails in an unacceptably high percentage of patients. Insights into pudendal neuroanatomy and pathophysiology offer improved microsurgical outcomes.Methods To evaluate results of a peripheral nerve approach to the pudendal nerve, 55 patients were prospectively evaluated. This cohort included 25 men and 30 women. Surgical approach was posterior, transgluteal if symptoms included rectal pain; or “anterior,” inferior pubic ramus approach if symptoms excluded rectal pain. Surgical approach was “resection,” if trauma created a neuroma, and “decompression,” if there were no neuroma. Effect of comorbidities was analyzed.Results At 14.3 months postoperatively, untreated anxiety/depression correlated with outcome failure, regardless of surgical approach, p < 0.002. There was no difference in results, men versus women, “anterior” versus “posterior” approach, or neuroma resection versus neurolysis. Success correlated with the “learning curve” of the surgeon. Self-rated success was significantly better (p < 0.0001) for patients operated on during the second year of the study than the first year of the study, and improved again in the final year of the study (p < 0.04), with 86% of the patients in final year achieving an excellent result and 14% achieving a good result.Conclusion There is hope for surgical relief from pudendal nerve problems by distinguishing neuroma from compression in the diagnosis, and then choosing a site-specific surgical approach related to which pudendal nerve branches are involved.
Keywords: pudendal nerve; neurolysis; neuroma